Development and retraction of a crossed retinal projection to the inferior colliculus in neonatal pigmented rats. - Cooper, A; Cowey, A (1990)
A transient aberrant projection from the retina to the contralateral inferior colliculus was demonstrated in pigmented rats in both whole-brains and sections following intra-ocular injection of horseradish peroxidase. The projection was prominent on the day of birth but reached its maximum density and extent after injection on day 1, when it covered at least a third of the inferior colliculus. It was absent or nearly absent by day 5. Its consistency, size, orderliness and systematic retraction suggest that it is not merely a developmental accident.